THE SIGNIFICANCE OF THE COMPLEMENTARITY PRINCIPLE WITHIN THE ROME STATUTE IN INTERNATIONAL CRIMINAL LAW - Heribertus Jaka Triyana (Fakultas Hukum Universitas Gadjah Mada, 2013)
In practice, the application of the complementarity principle in the Rome Statute remains unclear, particularly with respect to the prioritization of national penal law jurisdiction. This paper willdiscuss the relevance of the complementarity principle to the development of a national criminal justice system and to the investigation and prosecution of the most serious crimes provided for in the Statute. It was concluded that the complementarity principle should be used to unravel the twisted development of the national criminal justice system in accordance with the provisions of international law. We need to establish our national criminal justice system as the main and foremost forum (hence, willing and able) in the process of investigating and prosecuting the most serious crimes on earth. Dalam praktik, aplikasi Asas Pelengkap (the complementarity principle) dalam Statuta Roma masihbelum jelas, khususnya terkait dengan pengutamaan (prioritization) yurisdiksi hukum pidana nasional. Oleh karena itu, tulisan ini akan membahas relevansi asas tersebut terhadap pembangunan sistem hukum pidana nasional dan terhadap penyelidikan dan penuntutan kejahatan paling serius yang diatur dalam Statuta. Disimpulkan bahwa Asas Pelengkap harus Mahkamah digunakan sebagai pengurai benang kusutpembangunan sistem hukum pidana nasional Indonesia sesuai dengan ketentuan hukum internasional supaya menjadi forum utama (mau dan mampu) dalam proses penyelidikan dan penuntutan kejahatan paling serius di muka bumi.